Transformasi Kurikulum Pendidikan Islam Di Era Kecerdasan Buatan (Artificial Intelligence) - Angel, Dilla Anggela; Akip, Muhamad; Zohro, Nailul Padhil; Zohro, Miftahus Silmi (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2025)
The reformation of the Islamic education curriculum in the era of Artificial Intelligence (AI) reflects a serious call to align the educational system with the requirements of today’s rapidly evolving era, without neglecting the foundational values of Islam. This reform encompasses not only the substance of the curriculum but also pedagogical perspectives, teaching strategies, and the integration of technology as a supporting tool. The Indonesian government, through the Kurikulum Merdeka policy, has responded to this global necessity by creating space for the application of technology including AI to support a more personalized, adaptive, and solution-oriented learning process. In the context of Islamic education, AI can contribute by simplifying the study of classical texts, accommodating students’ individual learning styles, and streamlining educational administration efficiently. Today, the modern Islamic education curriculum focuses not only on mastering core Islamic sciences such as the Qur'an, Hadith, Fiqh, and Arabic, but also integrates general sciences, life skills, and the development of character and moral values (akhlaq). Fundamental principles such as integrity, balance, rububiyyah (God’s nurturing role), and the holistic development of the human being serve as the main framework in designing a curriculum with a comprehensive approach. The main challenge in AI integration lies in maintaining ethics, morality, and data security in its implementation so that it does not deviate from Islamic values. With the right approach, modern Islamic education in the era of AI is expected to produce a generation of individuals with noble character, global insight, and strong competitiveness.